2017
DOI: 10.1080/17538068.2017.1337604
|View full text |Cite
|
Sign up to set email alerts
|

Community-based participatory research through virtual communities

Abstract: Background: Over the last quarter century many new cyberspace platforms have emerged that facilitate communication across time, geographical distance and now even language. Whereas brick-and-mortar communities are defined by geographically local characteristics, a virtual community is an online community of individuals who socialize and connect around a common interest or theme using the Internet. Community-based participatory research (CBPR) is a public health approach that requires equitable partnerships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…In prior years, researchers attributed successes with virtual CBPR to breaking potential access barriers based on geographic and other factors (Tamí-Maury et al, 2017). In contrast, others have found that CBPR conducted remotely felt more disconnected due to a lack of physical interaction, inadequate technological skills or reduced access to secure internet, and complicated decision-making and other communication processes (Henderson et al, 2013;O'Brien et al, 2014;Tamí-Maury et al, 2017).…”
Section: Virtual Engagement With Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior years, researchers attributed successes with virtual CBPR to breaking potential access barriers based on geographic and other factors (Tamí-Maury et al, 2017). In contrast, others have found that CBPR conducted remotely felt more disconnected due to a lack of physical interaction, inadequate technological skills or reduced access to secure internet, and complicated decision-making and other communication processes (Henderson et al, 2013;O'Brien et al, 2014;Tamí-Maury et al, 2017).…”
Section: Virtual Engagement With Stakeholdersmentioning
confidence: 99%
“…In prior years, researchers attributed successes with virtual CBPR to breaking potential access barriers based on geographic and other factors (Tamí-Maury et al, 2017). In contrast, others have found that CBPR conducted remotely felt more disconnected due to a lack of physical interaction, inadequate technological skills or reduced access to secure internet, and complicated decision-making and other communication processes (Henderson et al, 2013;O'Brien et al, 2014;Tamí-Maury et al, 2017). In response to these challenges, the multiple modes of engagement that we leveraged allowed people to show up in ways that made sense for them as they, too, were getting used to what it meant to transition to remote work during a global pandemic (BBC Worklife, 2020).…”
Section: Virtual Engagement With Stakeholdersmentioning
confidence: 99%
“…The same thinking can be applied in the digital spiritual space. A koinonia will only be formed when people in the digital room are not merely present but also mutually connected in a digital community (Tamí-Maury et al, 2017). Therefore, the emotional experience can still be maintained.…”
Section: Internet Of Things and Its Influence In Koinoniamentioning
confidence: 99%
“…The new need for online learning in the context of COVID-19 COVID-19 lockdowns around the world have reduced the number of research studies where community members are involved despite the capacity for them to make meaningful contributions to policy making and building public trust [18]. Research suggests that appropriately designed online education can produce as good or better results than face-to-face learning, and there is a desire for some online education to continue post pandemic [19][20][21][22]. More research is needed to understand how to effectively adapt training and education in the context of COVID-19.…”
Section: Meaningfully Engaging Communities In Hiv Researchmentioning
confidence: 99%